Spillovers from high-value export agriculture on land use in developing countries: evidence from Madagascar - Minten, Bart; Randrianarison, Laila; Swinnen, Johan (Wiley, 2007)
High‐value agriculture for exports is increasingly important in developing countries. In a case study of contract farming for exports of vegetables from Madagascar, strong spillover effects of these trade opportunities on land use are found to exist. Using a matched plot sampling design, the productivity of rice—the main domestically consumed staple—is shown to be two‐thirds higher on fields that were contracted during the off‐season for the production of vegetables. This increase in yields is linked to an increase of soil fertility due to the application of fertilizer and compost, which farmers did not use prior to the contracts. Although agricultural output goes up significantly, labor productivity stays the same, suggesting that there is greater labor absorption on existing land and the diffusion of this type of technology at a larger scale throughout Madagascar would be expected to substantially decrease incentives to deforest by increasing wages and to boost productivity of existing lands relative to newly deforested ones.